Editorial: Exploring the need to include microbiomes into EFSA's scientific assessments. (29th June 2020) - Merten, Caroline; Schoonjans, Reinhilde; Di Gioia, Diana; Peláez, Carmen; Sanz, Yolanda; Maurici, Daniela; Robinson, Tobin
Abstract : The communities of microorganisms and their genomes in a defined environment are collectively referred to as microbiomes (Marchesi and Ravel, 2015). They include representatives from the Bacteria, Archaea, lower and higher Eukarya, and viruses, and are found in most environments such as soils, aquatic habitats, surfaces and specific lumen of plants, animals and humans. According to ongoing studies, microbiome structures and dynamics across the food system can have both direct and indirect effects on human and animal health, in addition to their impact on food quality, safety and sustainability (CNBBSV concept paper, 2019). Moreover, recent research projects have offered new insights into the associations between microbiomes and a wide range of human diseases as well as their possible impact in modulating the exposure to environmental chemicals. As one of the core tasks of EFSA is to assess risks to human and animal health and/or the environment from substances linked to food and feed production, the increasing understanding of the role of microbiomes in health calls for a prospective mapping of their roles into regulatory scientific assessment processes with a view to understanding their potential health impact.